Sequential Properties over Negative Pauli Pascal Table - Eunmi Choi; Jiin Jo (International Journal of Mathematics and Mathematical Sciences)
For polynomials x+yi and x+y−i satisfying the noncommutative multiplication yx=−xy, let C−1 and N−1 be the arithmetic tables, respectively. We investigate sequential properties of various diagonal sums over the tables C−1 and N−1 and prove that they are types of interlocked Fibonacci sequence and Padovan sequence.